Academic website for spreading uncertainties with AUV in hydrographic surveys - Barros, Anderson de Assis (2023)
Autonomous underwater vehicles (AUV) together with hydrographic mapping sensors contribute to the visualization and analysis of seabed features for various purposes. The volume of data obtained in hydrographic survey processing is a problematic issue. In this way, the project aims to develop an academic website applying the PHP programming language, with the purpose of evaluating the positional quality of coordinates obtained in hydrographic surveys with AUV, exposing more accurate results, for positional uncertainty values and positional quality. The project planning was segmented by stages: analysis of the algorithm and its development in the PHP programming language; the Cascading Style Sheets (CSS) language was used for the design; and corrections of eventual errors in the project development. As a result, the use of the site in several browsers, by means of desktop, did not present any problems in its functioning. However, something to be reviewed is the formatting of a layout that adjusts to different browsers on smartphones.